The Dynamics of Sectoral Labour Adjustment - Stephen Tapp (Queen's University, Department of Economics, 2007)
This paper develops an equilibrium search and matching model to jointly study the aggregate, sectoral, and distributional impacts of labour adjustment. The model extends Pissarides (2000) to include multisector production and search and "innovation" from investments that can potentially improve a match's productivity. These extensions deliver two mechanisms for inter-sectoral and intra-sectoral labour reallocation after shocks. First, because workers search simultaneously in multiple sectors, changes in labour market conditions in one sector propagate to impact wages and hiring in the rest of the economy through a reservation wage effect. Second, a positive productivity shock causes firms to invest more resources in innovation. This innovation effect shifts production towards high-skill jobs and amplifies the impact of productivity shocks relative to the baseline model. I show that the model is useful for analyzing labour adjustments caused by a diverse set of factors including: technological change; persistent energy price and exchange rate shocks; and trade liberalization. Finally, because the transition dynamics between steady-states are tractable, the model can be readily applied to the data to study particular labour adjustment episodes.
Keywords: E2; J6; J21; 330; Sectoral Labour Reallocation; Search and Matching; Wage Spillovers; Transition Dynamics; Arbeitsmarkt; Technischer Fortschritt; Wechselkurspolitik; Ölpreis; Schock; Branchenkrise; Arbeitsuche; Matching